Regulation of human neutrophil IL-1β secretion induced by Escherichia coli O157:H7 responsible for hemolytic uremic syndrome - Sabbione, Florencia (2023)
Shiga-toxin producing Escherichia coli (STEC) infections can cause from bloody diarrhea to Hemolytic Uremic Syndrome. The STEC intestinal infection triggers an inflammatory response that can facilitate the development of a systemic disease. We report here that neutrophils might contribute to this inflammatory response by secreting Interleukin 1 beta (IL-1β). STEC stimulated neutrophils to release elevated levels of IL-1β through a mechanism that involved the activation of caspase-1 driven by the NLRP3-inflammasome and neutrophil serine proteases (NSPs). Noteworthy, IL-1β secretion was higher at lower multiplicities of infection. This secretory profile modulated by the bacteria:neutrophil ratio, was the consequence of a regulatory mechanism that reduced IL-1β secretion the higher were the levels of activation of both caspase-1 and NSPs, and the production of NADPH oxidase-dependent reactive oxygen species. Finally, we also found that inhibition of NSPs significantly reduced STEC-triggered IL-1β secretion without modulating the ability of neutrophils to kill the bacteria, suggesting NSPs might represent pharmacological targets to be evaluated to limit the STEC-induced intestinal inflammation.